(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the cross-linguistic representation of the emotion of anger in English and Uzbek through idioms and phraseological units. The study aims to identify how anger is verbalized in the two languages, which semantic, figurative, and linguocultural mechanisms are involved, and what similarities and differences can be observed in their phraseological systems. The analysis shows that both English and Uzbek widely use figurative expressions to represent anger as an intense emotional state associated with bodily change, loss of emotional balance, verbal aggression, and sudden reaction. The study also reveals that anger-related phraseological units reflect not only emotional meaning, but also national-cultural and linguistic features of the two languages.